Post-COVID Pulmonary Mucormycosis: first case report from Bangladesh - Afroz, Farhana; Barai, Lovely; Rahim, Muhammad Abdur; Kanta, Shamima Sharmin; Hossain, Mohammad Delwar (Bangladesh Journal of Medicine, 2021)
Mucormycosis is an invasive fungal infection caused by different saprophytic environmental fungus occurring predominantly among immunosuppressed patients. Pulmonary mucormycosis is the second most common form after rhino-cerebral mucormycosis and may accompany with other infections. Coronavirus disease 2019 (COVID-19) itself and its treatment with immunosuppressive drugs and oxygen delivery systems etc. are setting the scenes for opportunistic and co-infections with fungus and other pathogens. A middle aged Bangladeshi man, with background diabetes mellitus, hypertension, bronchial asthma and COVID-19, presented with fever, respiratory symptoms and cavitary lung lesion. Diagnostic work-up confirmed pulmonary mucormycosis and he responded with liposomal amphotericin B. To the best of our knowledge, this is the first case of post-COVID mucormycosis reported from Bangladesh. Bangladesh J Medicine July 2021; 32(2) : 156-160